Respuesta :

Answer:

Option: B is the correct

Step-by-step explanation:

Step-by-step explanation:

We are given two matrices A and B as follows:

\begin{gathered}A=\left[\begin{array}{ccc}3&0\\2&-1\end{array}\right]\end{gathered}

A=[

3

2

0

−1

]

and

\begin{gathered}B=\left[\begin{array}{ccc}2&8\\0.6&3\end{array}\right]\end{gathered}

B=[

2

0.6

8

3

]

We know that the multiplication of two matrices of the type:

\begin{gathered}A=\left[\begin{array}{ccc}a&b\\c&d\end{array}\right]\end{gathered}

A=[

a

c

b

d

]

and

\begin{gathered}B=\left[\begin{array}{ccc}a'&b'\\c'&d'\end{array}\right]\end{gathered}

B=[

a

c

b

d

]

is given by:

\begin{gathered}AB=\left[\begin{array}{ccc}aa'+bc'&ab'+bd'\\ca'+dc'&cb'+dd'\end{array}\right]\end{gathered}

AB=[

aa

+bc

ca

+dc

ab

+bd

cb

+dd

]

Hence, here we have:

\begin{gathered}AB=\left[\begin{array}{ccc}3\times 2+0\times 0.6&3\times 8+0\times 3\\2\times 2+(-1)\times 0.6&2\times 8+(-1)\times 3\end{array}\right]\end{gathered}

AB=[

3×2+0×0.6

2×2+(−1)×0.6

3×8+0×3

2×8+(−1)×3

]

i.e.

\begin{gathered}AB=\left[\begin{array}{ccc}6+0&24+0\\4-0.6&16-3\end{array}\right]\end{gathered}

AB=[

6+0

4−0.6

24+0

16−3

]

i.e.

\begin{gathered}AB=\left[\begin{array}{ccc}6&24\\3.4&13\end{array}\right]\end{gathered}

AB=[

6

3.4

24

13

]